Systematic Review: Faktor Yang Berpengaruh Terhadap Implementasi Sistem Informasi Manajemen Rumah Sakit (SIMRS) - Yuvita Ratih Dewi; Ines Hediani Ikasari (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
The implementation of Hospital Management Information Systems (HMIS) is a crucial process in enhancing efficiency and information management in hospitals. This study conducts a literature review to analyze the factors influencing the implementation of HMIS. The factors examined include technology, organization, users, finance, and regulations. The aim of this research is to understand how these factors impact the implementation of HMIS in hospitals and how proper handling can enhance the success of the implementation. The findings of the literature review indicate that technology compatibility, leadership support, user training, adequate budget allocation, and compliance with regulations are significant factors in HMIS implementation. In conclusion, this research highlights the importance of considering these factors in planning and executing the implementation of HMIS in hospitals to achieve the desired benefits.